2007
DOI: 10.1071/ah070451
|View full text |Cite
|
Sign up to set email alerts
|

Integrated care facilitation for older patients with complex health care needs reduces hospital demand

Abstract: Objective: The evaluation of a new model of care for older people with complex health care needs that aimed to reduce their use of acute hospital services. Method:Older people (over 55 years) with complex health care needs, who had made three or more presentations to a hospital emergency department (ED) in the previous 12 months, or who were identified by community health care agencies as being at risk of making frequent ED presentations, were recruited to the project. The participants were allocated a "care f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 19 publications
0
71
0
Order By: Relevance
“…There were three randomized controlled trials [45], [47], [48], one quasi-experimental study with a control group [49], one quasi-experimental study without a control group [50], and one case-control study [46]. Two studies were from Australia [47], [49], and the rest of the studies were from the US [45], [46], [48], [50].…”
Section: Resultsmentioning
confidence: 99%
“…There were three randomized controlled trials [45], [47], [48], one quasi-experimental study with a control group [49], one quasi-experimental study without a control group [50], and one case-control study [46]. Two studies were from Australia [47], [49], and the rest of the studies were from the US [45], [46], [48], [50].…”
Section: Resultsmentioning
confidence: 99%
“…In one study, performed in the USA, people received a booklet with general information on when to visit an ED, but this did not show a significant effect on the number of ED-visits [41]. Education directed at specific conditions (ear pain in children, diabetes, asthma) and more intensive programs for geriatric or older, chronically ill patients have shown mixed results [4247]. The effect of telephone consultation for patients to call for advice about their current health symptoms prior to seeking treatment at the ED also seems insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…25 Bird et al similarly reported a 20.8% reduction in AED visits after educating patients in aspects of self-management. 26 These reductions could be due to inappropriate users of the facilities seeking alternative sources of care such as primary health centres, community pharmacists and general practitioners. Considering the small population of physicians in Nigeria, educational intervention has to be the duty of all health care providers to avoid physicians being overwhelmed by the large number of patients.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%